2016
DOI: 10.1007/s12663-016-0881-y
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Radiotherapy for Head Neck Cancer

Abstract: Changes in patient anatomy may occur either from a tumour volume, position or function of a specific organ at risk, or target volume, weight loss or a reduction in postoperative oedema, and may vary between patients. Adaptive radiotherapy aims to correct morphological variations by realizing one or more plans during the treatment course. Imaging is used to detect these variations, thereby deciding on a potential replanning. At present, adaptive radiotherapy for head neck cancer (HNC) mainly deals with treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…8 According to Liu et al9, tumor shrinkage can be detected as early as the first two weeks, with median revealed shrinkage rates varying from 3 to 16%, 9 Surcus et al 5 found that tumor size was reduced by the end of the fourth week, with median revealed shrinkage rates ranging from7 to 48%, 5 while Loo et al 10 discovered that the tumor size had shrunk by the end of the 7th week, with median disclosed shrinkage rates varying from 6 to 66%. 10 In our study we found that median primary tumor volume changed from (48.3) cm 3 to (31.26) cm 3 with percentage reduction about (35.2%) at the end of 4th week.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…8 According to Liu et al9, tumor shrinkage can be detected as early as the first two weeks, with median revealed shrinkage rates varying from 3 to 16%, 9 Surcus et al 5 found that tumor size was reduced by the end of the fourth week, with median revealed shrinkage rates ranging from7 to 48%, 5 while Loo et al 10 discovered that the tumor size had shrunk by the end of the 7th week, with median disclosed shrinkage rates varying from 6 to 66%. 10 In our study we found that median primary tumor volume changed from (48.3) cm 3 to (31.26) cm 3 with percentage reduction about (35.2%) at the end of 4th week.…”
Section: Discussionsupporting
confidence: 46%
“…The whole study group received IMRT radiation therapy with concurrent weekly cisplatin 40mg/m2, target volume coverage of original and boost plan on primary CT (P1), also doses to organs at risk (ipsilateral parotid, contralateral parotid, spinal cord as well as brain stem) are displayed in table (2) The modified IMRT plan increased GTV and PTV2 median coverage by 0.25% and 0.1.27%, respectively; ipsilateral and contralateral parotid volumes were reduced by 13.26% and 17.68%, respectively. Table (3) The median dose decrease to the ipsilateral parotid, contralateral parotid, spinal cord, and brain stem was 3.86%, 5.32%, 3.5%, and 5.28%, respectively, with adaptive replaning. The median coverage for GTV and PTV2 was improved by 0.25% and 0.1.27%, respectively, with the adapted IMRT plan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most implementations of DIR involve a transformation that establishes a geometric correspondence between fixed and moving images, an objective function, and an optimization approach to maximize the similarity between images [12][13][14]. Importantly, even minor differences in patient anatomy can result in devastating dose administration in HNC [4,15], highlighting the need for consistent image co-registration when propagating segmentations of target volumes and OARs for radiotherapy treatment planning. Therefore, determining the impact of post-acquisition registration techniques (i.e., DIR) on multisequence MRI acquisitions is crucial for MR-guided treatment of HNC.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, RT has relied on radiographic images to enable pre-treatment segmentation of target volumes and nearby organs at risk (OAR) to plan intensity-modulated doses [2,3]. However, throughout RT, the dynamic changes in target volumes and OARs and patientspecific changes (e.g., weight loss) can lead to unintended doses of radiation to OARs and subsequent debilitating side effects [4]. These potential unintended doses are particularly relevant for HNC because the head and neck region is home to various complex, highly radiosensitive structures and tissue interfaces that can drastically change during RT [4,5].…”
Section: Introductionmentioning
confidence: 99%